PENERAPAN METODE KERJA KELOMPOK DALAM MENINGKATKAN HASIL BELAJAR MUATAN IPS TENTANG PERISTIWA KEBANGSAAN MASA PENJAJAHAN DI SEKOLAH DASAR - Nisa, Annisa Qomariah; Putri Alfadillah, Suhaimi (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2023)
The purpose of this classroom action research in general is to improve social studies content learning outcomes about national events of the colonial masses by using the group work method. This classroom action research was carried out in 2 cycles using the group work method. Each cycle has 4 stages, namely planning, action, observation and reflection. The research subjects totaled 24 students. The results obtained after class action research on student learning outcomes on social studies content regarding colonial mass national events in class VB SDN 018 Samarinda Ulu could increase through the group work method in learning. This can be seen from the evaluation results of cycle I, there were 13 students who completed with an average of 66.5 or a percentage of classical completeness of 54%. In Cycle II, there were 24 students who completed with an average of 86 or 100% classical completeness percentage. Group work provides students with greater opportunities to explore the talents they have, and they also get friends who are considered better and more appropriate to study together, so that they can easily master all the knowledge they expect. The purpose of the group work method is that group work can develop students' abilities in terms of suggestion, motivation, and information, train and develop students' potential in integrating relationships with others, foster a sense of togetherness by working together in solving a problem or work from educators, train students' courage, to solidify the knowledge students have acquired. Keywords: group work, improving learning outcomes, social studies content